Deep Sclerectomy with Low-Tension Sutures versus Tight-Tension Sutures without Space-Maintaining Implant in Controlling Intraocular Pressures: 10.36351/pjo.v36i4.1031 - Zia, Rashid; Jain, Nikhil; Dardzhikova, Albena (Pakistan Journal of Ophthalmology, 2020)
Purpose: To compare the IOP lowering effect and post-operative complications of low tension sutures versus tight tension sutures in deep sclerectomy. Study Design: Quasi experimental study. Place and Duration of Study: Methods: Twenty seven eyes undergoing deep sclerectomy operation with normal strength sutures (TS) were compared with 21 eyes undergoing a modified technique in which low tension sutureswere tied to only approximate anatomy (LS). Both sets of patients were operated on by the same experienced surgeon with similar technique except for the tensile strength of suture; same antimetabolite in similar concentration was used with identical pre and post-operative care. Outcome measures were post-operative intraocular pressure, number of medications needed and complications. Results: IOP decreased significantly in both groups, in TS group by 12.6 mm Hg (p < 0.001) and in the LS groups by 18.9mm Hg (p < 0.001). Greater IOP drop was seen in LS group versus TS group (p = 0.046). In LS group number of eye drops required post operatively were significantly less than TS group (p = 0.007). After follow up only one patient in the loose suture group still required IOP-lowering medication. There were minimal complications in both groups, 1 patient in the LS group and 7 in TS group required a YAG Goniotomy. Conclusion: Using low tension sutures in deep sclerectomy increases the IOP lowering effect of the surgery and reduces the number of medications the patient requires post operatively.